Plasma-Enabled Smart Nanoexosome Platform as Emerging Immunopathogenesis for Clinical Viral Infection - Seyyed Mojtaba Mousavi; Seyyed Alireza Hashemi; Ahmad Gholami; Masoomeh Yari Kalashgrani; Neralla Vijayakameswara Rao; Navid Omidifar; Wesley Wei-Wen Hsiao; Chin Wei Lai; Wei-Hung Chiang (MDPI AG, 2022)
Smart nanoexosomes are nanosized structures enclosed in lipid bilayers that are structurally similar to the viruses released by a variety of cells, including the cells lining the respiratory system. Of particular importance, the interaction between smart nanoexosomes and viruses can be used to develop antiviral drugs and vaccines. It is possible that nanoexosomes will be utilized and antibodies will be acquired more successfully for the transmission of an immune response if reconvalescent plasma (CP) is used instead of reconvalescent plasma exosomes (CPExo) in this concept. Convalescent plasma contains billions of smart nanoexosomes capable of transporting a variety of molecules, including proteins, lipids, RNA and DNA among other viral infections. Smart nanoexosomes are released from virus-infected cells and play an important role in mediating communication between infected and uninfected cells. Infections use the formation, production and release of smart nanoexosomes to enhance the infection, transmission and intercellular diffusion of viruses. Cell-free smart nanoexosomes produced by mesenchymal stem cells (MSCs) could also be used as cell-free therapies in certain cases. Smart nanoexosomes produced by mesenchymal stem cells can also promote mitochondrial function and heal lung injury. They can reduce cytokine storms and restore the suppression of host antiviral defenses weakened by viral infections. This study examines the benefits of smart nanoexosomes and their roles in viral transmission, infection, treatment, drug delivery and clinical applications. We also explore some potential future applications for smart nanoexosomes in the treatment of viral infections.